The effects of service dogs for children with autism spectrum disorder and their caregivers: a cross-sectional study - Rodriguez, Kerri E.; Rispoli, Mandy; Kelleher, Bridgette L.; MacLean, Evan L.; O’Haire, Marguerite E. (Frontiers in Psychiatry, 2024)
Service dogs are an increasingly popular complementary intervention for children with autism spectrum disorder. However, despite increasing demand, there remains a lack of empirical research on their potential benefits. The purpose of this study was to evaluate the effects of service dogs on children with autism and their caregivers. A total of N = 75 families of children with autism were recruited from a non-profit service dog provider in the US, including n = 39 families previously placed with a service dog and n = 36 families engaging in usual care while on the waitlist. Caregivers completed an online survey containing both self-and proxy-report standardized measures of child, caregiver, and family functioning. Linear regressions modeled the relationship between service dog presence and survey outcomes, controlling for relevant child and caregiver covariates. Results indicated that having a service dog was associated with significantly better child sleep behaviors, including better sleep initiation and duration and less sleep anxiety/co-sleeping with medium effect sizes. However, service dog presence was not significantly related to child withdrawal, negative emotionality, emotional self-control, hyperactivity, irritability, and lethargy with small effect sizes. For caregivers, having a service dog was not significantly related to standardized measures of caregiver strain, sleep disturbance, depression, or the impact of the child's condition on family functioning with small effect sizes. Supplemental matched case-control analyses confirmed these findings. In conclusion, service dogs were found to positively impact sleep behaviors among children with autism, but may not uniformly relate to other areas of child and caregiver wellbeing. Prospective longitudinal designs, larger sample sizes able to detect small effects, and studies that measure sleep using objective methods are needed to build on these findings.